Ferrous Wheel Hypothesis: Abiotic nitrate incorporation into dissolved organic matter. (15th January 2019) - Matus, Francisco; Stock, Svenja; Eschenbach, Wolfram; Dyckmans, Jens; Merino, Carolina; Nájera, Francisco; Köster, Moritz; Kuzyakov, Yakov; Dippold, Michaela A.
Graphical abstract: Highlights: Abiotic nitrate incorporation into DON enhances N-retention in temperate rainforest. About 25% of 15 N-nitrate was transformed to DON supporting Ferrous Wheel Hypothesis. New N-cycle model is proposed where Ferrous Wheel Hypothesis is included. N2 O provided further evidence of NO3 − reduction and CO2 of DOM oxidation. Abstract: We evaluated the abiotic formation of dissolved organic nitrogen (DON) by the fast reaction of iron (Fe) with nitrate (NO3 − ) in the dissolved organic matter (DOM) of volcanic soils in a temperate rainforest (>5000 mm precipitation per year). During five days, the educts and products of abiotic reactions under anoxic conditions were measured in a microcosm experiment depending on the Fe and NO3 − concentrations. A control zero-Fe was not used because there was no chemical reaction with nitrate addition. Using a novel technique of automated sample preparation for inorganic N (SPIN) attached to a membrane inlet quadrupole mass spectrometry (MIMS), the 15 N abundances and inorganic N concentrations were determined directly in aqueous solutions. The results were explained in the context of the Ferrous Wheel Hypothesis which states that Fe(II) is utilized to reduce NO3 − to nitrite (NO2 − ) that is incorporated into DOM. Fe(II) is regenerated from Fe(III) in anaerobic soil microsites. Here we tested one part of this hypothesis, the processes occurring in DOM (instead of soil organic matter). Using the SPIN-MIMS technique, we could overcome Ferrous Wheel Hypothesis criticism regarding possible Fe interference during NO3 − analysis. The total recovery of 15 N added as NO3 − fluctuated between 63 and 101%, and the remaining 15 N was measured as gaseous N2 O. The 15 N-labelled NO3 − added decreased immediately after 15 min of incubation. After five days of incubation, approximately 25% of the labelled NO3 − (e − acceptors) added was transformed to DON in the presence of a high amount of Fe(II) (e − donors). Small amounts of N2 O and CO2 provided further evidence of NO3 − reduction and DOM oxidation, respectively. From these results, we propose a new theoretical model that includes the Ferrous Wheel Hypothesis, where only the transformation of NO3 − to DON was proven. The present results explain the high retention of NO3 − in DOM from volcanic soils in ecosystems with high precipitation.